2020
DOI: 10.3389/fcimb.2020.594288
|View full text |Cite
|
Sign up to set email alerts
|

Role of the PE/PPE Family in Host–Pathogen Interactions and Prospects for Anti-Tuberculosis Vaccine and Diagnostic Tool Design

Abstract: The pe/ppe genes are found in pathogenic, slow-growing Mycobacterium tuberculosis and other M. tuberculosis complex (MTBC) species. These genes are considered key factors in host-pathogen interactions. Although the function of most PE/PPE family proteins remains unclear, accumulating evidence suggests that this family is involved in M. tuberculosis infection. Here, we review the role of PE/PPE proteins, which are believed to be linked to the ESX system function. Further, we highlight the reported functions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 89 publications
4
30
0
Order By: Relevance
“…The proteomics data indicated that the mycomembrane-associated PPE/PE family proteins were remarkably greater in number in the PL cells than in the PBFs or SBFs, indicating that Mmr in a single-cell state could more readily interact with the host and modulate the host immune response and/or nutrient transport ( 49 , 50 ). PL cells were cultured in the presence of Tween 80, which, in detaching the mycobacterial capsule ( 17 ), most likely helped identify these immunogens.…”
Section: Discussionmentioning
confidence: 99%
“…The proteomics data indicated that the mycomembrane-associated PPE/PE family proteins were remarkably greater in number in the PL cells than in the PBFs or SBFs, indicating that Mmr in a single-cell state could more readily interact with the host and modulate the host immune response and/or nutrient transport ( 49 , 50 ). PL cells were cultured in the presence of Tween 80, which, in detaching the mycobacterial capsule ( 17 ), most likely helped identify these immunogens.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on TB subunit vaccines have provided a large number of vaccine candidate antigens for peptide-based vaccines development, such as Ag85A (Rv3804c) ( 241 ), Ag85B (Rv1886c) ( 116 , 202 , 239 , 240 ), 6-kDa early secretory antigenic target (ESAT-6, Rv3875) ( 222 , 223 , 238 , 239 ), heat shock protein HspX (also known as Hsp16.3, Acr, and 14 kDa antigen, Rv2031c) ( 115 , 146 , 202 , 210 , 211 , 242 ), TB10.4 (Rv0288) ( 2 , 115 , 211 , 240 ), Rv0476 ( 211 ), Hsp65 ( 202 ), 19-kDa lipoprotein (Rv3763) ( 202 ), Rv1733c ( 202 , 203 ), PE/PPE proteins ( 2 , 243 , 244 , 248 ), MPT64 (Rv1980c) ( 246 , 247 ), Mtb8.4 ( 2 ), and resuscitation-promoting factors (Rpfs) ( 2 , 228 ). These antigens have been reported to be attractive vaccine candidates for preventing and controlling TB.…”
Section: Research Status Of Tb Peptide-based Vaccinesmentioning
confidence: 99%
“…The proteomics data indicated that the mycomembrane-associated PPE/PE family proteins were remarkably greater in number in the PL than in the PBFs or SBFs, indicating that Mmr in a single cell state could more readily interact with the host, and modulate the host immune response and/or nutrient transport (49, 50). PL cells were cultured in the presence of Tween-80, which, in detaching the mycobacterial capsule (17), most likely helped identify these immunogens.…”
Section: Discussionmentioning
confidence: 99%